2011
DOI: 10.1111/j.1420-9101.2011.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Wings or winds: inferring bat migration in a stepping-stone archipelago

Abstract: Eocene ocean currents and prevailing winds correlate with over‐water dispersals of terrestrial mammals from Africa to Madagascar. Since the Early Miocene (about 23 Ma), these currents flowed in the reverse direction, from the Indian Ocean towards Africa. The Comoro Islands are equidistant between Africa and Madagascar and support an endemic land vertebrate fauna that shares recent ancestry predominantly with Madagascar. We examined whether gene flow in two Miniopterus bat species endemic to the Comoros and Mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…It has been demonstrated that two species of Miniopterus are shared between Madagascar and the Comoros [58], [59] and include M . griveaudi and M .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that two species of Miniopterus are shared between Madagascar and the Comoros [58], [59] and include M . griveaudi and M .…”
Section: Discussionmentioning
confidence: 99%
“…griveaudi and M . gleni , there is no pronounced phylogeographical structure [7], [36], [37]. Hence, it can be assumed that these bat species undergo considerable dispersal, which also may explain the lack of nycteriibid host specificity and geographical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Volant species show relatively low African source bias, suggesting they are not strongly influenced by ocean current direction. Of greater relevance to volant species are prevailing wind direction (42) and the pattern and frequency of storms. Volant taxa of Asian origin may have used stepping stones, such as India, or the Seychelles, Andaman, or Mascarene islands.…”
Section: Discussionmentioning
confidence: 99%